Sarcoid-like paracoccidioidomycosis: case report - Athayde, Carlos Arthur de Figueiredo; Nacif, Caroline Cruz Barbosa; Lupi, Omar; Lima, Ricardo Barbosa; Lyra, Marcelo Rosandiski; D’Acri, Antônio Macedo; Martins, Carlos José (Medicina (Ribeirao Preto), 2017)
Paracoccidioidomycosis (PCM), which is caused by the dimorphic fungus Paracoccidioides spp, is the most prevalent systemic mycosis in immunocompetent individuals in Brazil. The fungus lives in the soil and usually infects the patient through inhalation of airborne propagules, the lungs being the portal of entry. In areas of larger endemicity, such as Brazil, the annual incidence reaches 3 cases per 100,000 inhabitants. Cutaneous lesions in PCM are frequent and ulcer or ulcerous-vegetative lesions are the commonest morphological type, followed by the infiltrative pattern. The histology shows a dermal granulomatous inflammation. Infiltrative PCM can be easily misdiagnosed, once clinical and histological similarities may occur specially with cutaneous sarcoidosis. We describe a case of cutaneous paracoccidioidomycosis misdiagnosed as sarcoidosis both in clinical examination and in the histopathological analysis. Further exams confirmed Paracoccidioides sp. as the causative agent through mycological cultures and Grocott’s stain. We believe this case may help physicians around the world to suspect and consider PCM as a differential diagnosis, especially if the patient has traveled to endemic area or the current therapy for sarcoidosis lacks clinical improvement.